The Effect of Implementing 12/14 Day Harvest Rotation on FFB Production and Harvest Employee Income: Case Study at PT Nusaina Agro Kobi Manise - Memem, Jusri; Girsang, Wardis; Damanik, Inta PN (Future Science / FSH-PH Publications, 2024)
The policy regarding crop rotation is relatively new. However, this policy is still being debated, because it is not yet known that a consistent harvest rotation pattern has a significant effect on harvest premiums, FFB production and harvest employee income at PT Nusaina Agro Kobi Manise. This research aims to analyze the effect of 12/14 day harvest rotation and harvest premiums on FFB production and harvest employee income. This research uses quantitative descriptive methods. Data were analyzed using SmartPLS 3.0 Software. The results of the research show the effect of implementing 12/14 day harvest rotation and harvest premiums on FFB production and harvest employee income. It is clear that implementing 12/14 day harvest rotation does not have a direct influence on FFB production and harvest employee income but the implementation of 12/14 day harvest rotation days have an indirect influence through harvest premiums on production and harvest employee income. The t-calculated path coefficient value of 12.140 is greater than the t-table value of 1.96 with a p-value of 0.00 which is smaller than 0.05 so that the variable implementing 12/14 day harvest rotation has a significant effect on the harvest premium variable. The specific indirect effect value of implementing a 12/14 day harvest rotation has an effect on the harvest premium and in turn has an effect on FFB production with a calculated t-value of 2.500 which is greater than the t-table value of 1.96 and with a p-value of 0.013 which is smaller than 0.05 so can be said to have a significant effect.